PENDIDIKAN KARAKTER BAGI PELAKU PEDOFILIA (SEBUAH STRATEGI DALAM MENGATASI AMORAL) - Cahyono, Heri; Suhono, Suhono; Khumairo, Aisyah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
High intensity sexual violence of children in Indonesia, especially pedophilia has taken a lot of attention among academics and society. The aim of this research was to provide insights and thoughts about education character for pedophile actors as a strategy in dealing with immoral problems, and expected to be a reference as society and academics in implementing character education among pedophiles. This reserach was a literature review that sees pedophiles as serious issues that need to be resolved quickly through the concept of education character. Where educators in carrying out character education need to use some strategies such as moral feeling and loving, moral acting, moral modeling and repentance (back) to our God.